The Impact of Merger and Acquisition on Customer Satisfaction in Post- Merger Phase in Banking Sector of Nepal - Sharma, Krishna Prasad (Journal of Nepalese Business Studies, 2018)
Mergers and acquisitions among financial institutions have been increased due to the introduction of merger by-law in May 2011 and capital enhancement through monetary policy of Nepal Rastra Bank in 2015. Bank and financial institutions need to be fully approachable and reactive that banking merger has not hampered customer service. Since the entire business depends on the customer’s positive feedback and satisfaction, good customer service is essential in this kind of business. It is always being argued that the impact of mergers and acquisitions on the customer is difficult to measure due to the direct influence of external factors like global competition or technological advancement. Bearing this consideration, the paper evaluates the impact of bank mergers and acquisitions on customers by using survey method. Customer satisfaction and service quality after mergers have been measured by summative scale calculated by a simple arithmetic mean and by using the weighted average method. Similarly, five point Likert-type scales have been used for measuring the satisfaction level of customer. Customers were asked to rank the various factors affecting satisfaction level on the five point scale which was further analyzed using SPSS and MS Excel. Results suggest that the merger program was successful from customers’ point of view in Nepal because it has benefited them through economies of scale, expansion of working area and advancement in technology. Another perspective regarding the service quality of banks in post-merger found that customers are enjoying competitive interest rate due to the enhanced capital base.